Perivascular adipocyte size is related to the lipid profile and inflammatory changes in a healthy population - Bartuskova, Hana; Kralova Lesna, Ivana; Kauerova, Sona; Lanska, Vera; Fronek, Jiri; Janousek, Libor; Muffova, Barbora; Paukner, Karel; Poledne, Rudolf (Adipocyte, 2025)
Inflammatory changes in perivascular adipose tissue are associated with atherosclerotic lesions in the adjacent artery and can also be used as a marker in patient workup. While adipocyte size is known to be closely related to adipose tissue dysfunction and inflammation, it has not been widely studied in perivascular adipose tissue obtained from healthy human subjects without clinical atherosclerosis. In this cross-sectional study, we addressed this issue by measuring adipocyte size and defining its relationship to cardiovascular risk factors in a healthy cohort of living kidney donors. The presence of cardiovascular risk factors was established by a standardized questionnaire, clinical measurements and body composition analyses. Adipocyte size was measured in the perivascular depot. The proportions of various macrophage subtypes were determined by flow cytometry. To confirm the results, the proportion of CD68 + macrophages was additionally assessed by immunohistochemistry. A correlation and principal component analyses were performed to explore associations. Adipocyte size in perivascular adipose tissue correlated with markers of lipid metabolism, inflammation, and glucose metabolism. Further, the positive correlation with the pro-inflammatory subpopulation of macrophages suggests a strong local effect of perivascular adipose tissue. Perivascular adipocyte size was associated with cardiovascular risk factors and markers of inflammation in a healthy cohort of living kidney donors. This further supports the local role of adipose tissue dysfunction and inflammation in early atherosclerosis development and detection.
Keywords: Adipocytes; adipocyte size; Cross-Sectional Studies; tukové buňky; lipidy; Inflammation; zánět; Middle Aged; inflammation; mužské pohlaví; průřezové studie; Adult; macrophages; Cell Size; cardiovascular risk factors; velikost buňky; Lipids; Macrophages; Lipid Metabolism; ženské pohlaví; Humans; metabolismus lipidů; lidé středního věku; Adipose Tissue; makrofágy; Perivascular adipose tissue; dospělí; Female; tuková tkáň; lidé; Male